Characterization, Isolation, and Culture of Mouse and Human Spermatogonial Stem Cells. Issue 4 (April 2014) - Guo, Ying; Hai, Yanan; Gong, Yuehua; Li, Zheng; He, Zuping
Abstract Spermatogenesis is a special process by which spermatogonial stem cells (SSCs) divide and differentiate to male gametes called mature spermatozoa. SSCs are the unique cells because they are adult stem cells that transmit genetic information to subsequent generations. Accumulating evidence has demonstrated that SSCs can be reprogrammed to acquire pluripotency to become embryonic stem‐like cells that differentiate into all cell lineages of the three germ layers, highlighting potential important applications of SSCs for regenerative medicine. Recent studies from peers and us have made great achievements on the characterization, isolation, and culture of mouse and human SSCs, which could lead to better understanding the biology of SSCs and the applications of SSCs in both reproductive and regenerative medicine. In this review, we first compared the cell identity and biochemical phenotypes between mouse SSCs and human SSCs. Notably, the cell types of mouse and human SSCs are distinct, and human SSCs share some but not all phenotypes with mouse SSCs. The approaches for isolating SSCs as well as short‐ and long‐term culture of mouse SSCs and short‐period culture of human SSCs were also discussed. We further addressed the new advances on the self‐renewal of SSCs with an aim to establish the long‐term culture of human SSCs which has not yet been achieved. J. Cell. Physiol. 229: 407–413, 2014. © 2013 Wiley Periodicals, Inc.